Volpocalypse Now. Issue 108 (30th July 2020) - Lewis, Alan L.
Abstract : Last year Alan Lewis published a paper, Option‐based Equity Premiums, proposing that GARCH approaches to equity risk premiums be abandoned and work on the problem could be done more effectively free of models. Tragically, in the early months of 2020, the markets presented an ideal opportunity to apply the approach of the 2019 paper. In this issue we publish Alan's findings on US Equity Premiums during the COVID‐19 Pandemic. Dan Tudball speaks to the author.